Controle estatístico aplicado ao processo de colheita mecanizada diurna e noturna de cana-de-açúcar - Noronha, Rafael Henrique de Freitas [UNESP]; da Silva, Rouverson Pereira [UNESP]; Chioderoli, Carlos Alessandro [UNESP]; dos Santos, Edvaldo Pereira [UNESP]; Cassia, Marcelo Tufaile [UNESP] (FapUNIFESP (SciELO), 2011)
The system of mechanized harvesting can seek process improvements using quality tools that can assist in reducing losses, damaged ratoons and increase the longevity of sugarcane crop. Therefore, the objective this study was to detect the effective control of the variability of losses and damage to ratoon and identify whether they are within acceptable standards. Thus, 40 points were sampled in two periods of harvest, diurnal and nocturnal, in rectangular grids (55 × 45 m) for determining visible losses (whole and shattered billets, fixed and loose piece, stump and shrapnel), using frames of 10 m 2. Also, we measured the height of cut and degree of damage to ratoon (without damage, partial injury and fragmentation). The statistic used was descriptive variables for the loss of sugarcane during the diurnal (D) and nocturnal (N) periods, analysis of variance using the F test at 5% probability and the Tukey test for comparison ofthe mean, also using the statistical control through charts process. There was no difference to ratoon damage. In the process of harvest, losses of whole and shattered billets by grinding were considered under control, so as losses from the stump. On the other hand, the losses of fixed piece, shrapnel and whole-cane were not controlled. The cutting height and total losses were higher during the nocturnal harvest. The charts were shown to be effective for the evaluation of control process of diurnal and nocturnal harvests.
Statistical control applied in the process of mechanical sugar cane harvest in the diurnal and nocturnal periods
Keywords: Harvester; Quality control; Visible losses